Job Performance of Traffic Police Officers in North Maluku The Role of Work Discipline and Competence - Ibrahim, Sri Martati S.; Marwan, Marwan; Milwan, Milwan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates the extent to which work discipline and professional competence contribute to the performance of traffic police officers within the Directorate of Traffic Police, North Maluku Regional Police (Ditlantas Polda Maluku Utara). The research addresses a critical gap in understanding how behavioral and skill-based factors jointly influence law enforcement performance in emerging regional contexts. Methodology: Employing a quantitative research design, data were collected from a sample of 187 respondents, determined using Slovinâ€™s formula from a total population of 340 officers. Structured questionnaires served as the primary instrument, and multiple linear regression analysis was used to examine the relationships among variables. Results: The analysis confirms that both work discipline and competence exert a statistically significant influence on officer performance. Findings: Among the predictors, professional competence demonstrated the strongest effect (t = 11.511), indicating a direct and substantial contribution to performance outcomes. Interestingly, while work discipline was also significant (t = 3.790), its negative coefficient suggests that overly rigid enforcement may hinder rather than enhance performance. The model accounts for 41.9% of the variance in performance (F = 66.427; p < 0.001; RÂ² = 0.419). Novelty: This study offers a novel perspective by integrating behavioral rigidity and competency frameworks within a single performance evaluation model for traffic police. Originality: The research provides original empirical evidence from a regional policing context in Indonesia, advancing theoretical and practical insights into performance management in public sector organizations. Conclusion: Enhancing professional competence, coupled with a more adaptive approach to discipline, represents a strategic pathway for improving law enforcement performance. Type of Paper: Research article.